Prevalence of intestinal metaplasia and dysplasia in infectious and non-infectious chronic gastritis - Hassawi, Bashar Abdul-Jabbar; Khalil, Khesar Hussein; Sharafadin, Zobayda Adnan (International Journal of Research in Medical Sciences, 2017)
Background: Objective of current study was to estimate the prevalence of intestinal metaplasia in dyspeptic patients in Duhok (Kurdistan region) and its association with H. pylori and dysplasia according to gender and age. Methods: This was a prospective observational study. Study was conducted from Jan 2012 to Jul 2014 at Azadi Teaching Hospital Duhok City. A total number of 205 antral gastric biopsies were collected in Azadi GIT-Centre and examined histologically to detect intestinal metaplasia. These biopsies were stained by Giemsa to detect H. pylori organisms. Results: H. pylori was found in 94 (46%) patients while intestinal metaplasia in general was found in 30 (15%) patients; (9.8% in association with H. pylori) and (4.7% without H. pylori). Among intestinal metaplasia 6 cases show dysplasia (6/205 = 3%). Conclusions: This study has documented mainly that the prevalence of intestinal metaplasia is significant among patients (In Duhok) with chronic gastritis and mainly in those patients who are positive for H. pylori with an active chronic gastritis. Intestinal metaplasia mostly affects patients above the age of 40 years with no significant gender difference.